COGNITIVE ADAPTATION IN DOWN SYNDROME CHILDREN'S MOTHERS - Romero, Rosalinda; Morillo, Beatriz (Anales de Psicología / Annals of Psychology, 2002)
he current investigation was conducted to determine the Cognitive Adaptation (AC) in Down Syndrome (SD) children’s mothers. The research was a descriptive study based on AC theory created by S.E. Taylor (1983) wich explain the adjustment mechanism to threatening events. It used a sample with 83 DS’s mothers who attended at educational centres in Zulia State of Venezuela. The instruments used was AC for SD Scale (ACODOWN, 1999) and Scale of Graffar. The results obtained indicatesthat 49% of mothers has a medium-high level of AC with an average of 5.140.42. In the AC process us founded that effort recovering self-esteem dimension had a high contribution (5.470.62), in second place gaining of control (5.020.75) and lately sense of searching (4.900.78). This research concluded that SD children’s mothers withages between 0-6 year old have AC and after the initial crisis have hope in the satisfactory evolution of his children, making actions to get mastery in this event.